THE EFFECT OF FINANCIAL LEVERAGE AND CASH FLOW ON THE FINANCIAL DISTRESS OF INFRASTRUCTURE SECTOR COMPANIES - Dwi Fitrianingsih; Mega Arum; Eny Suheny (Jurnal Ekonomi, 2022)
This study aims to determine the effect of Financial Leverage and Cash Flow on Financial Distress in infrastructure sector companies on the IDX. This type of research is quantitative research and uses secondary data. The sampling technique used the purposive sampling technique, with a total population of 31 companies obtained as a sample of 155. The analytical method used in this study was multiple linear analysis. The results of the analysis that have been carried out show that financial leverage has an influence on financial distress with a count of -7.159 with a significance value of <0.05 so the first hypothesis is accepted. Cash flow has no effect on financial distress with a count of 1.663 and a significance value of >0.05 so the second hypothesis is rejected. Simultaneously, financial leverage and cash flow affect financial distress with an F test value of 29.185. Based on the R2 test that has been carried out, the magnitude of the distribution that affects financial distress is 35.1%. So this study shows that financial leverage harms financial distress. Cash flow does not affect financial distress. Financial leverage and cash flow can simultaneously affect financial distress,